The implementation of the integrated performance assessment (IPA) model to improve English students' speaking skills - Ildi Kurniawan; Syafrizal Sabaruddin; Azhar Aziz Lubis (UNIB Press, 2022)
This study aims to analyze the extent to which the application of the IPA model could improve Indonesian students’ speaking skill, especially speaking skills for discussion course. It was classroom action research in which the stages of its activities include planning, implementation, evaluation, and reflection. This research’s subjects were the third semester English Department University of Bengkulu. The researchers only took four cycles as the data of the research. Qualitative and quantitative data were analyzed to find a valid conclusion. The results show that the application of the IPA model improved the basic skills of students’ speaking skills in class. It can be seen from the improvement in almost every cycle. The mean score in cycle 1 was 80, followed by 80.3 in cycle 2, but slightly decreased in cycle 3 with a mean score of 79.6 and got higher again in cycle 4 with a mean score of 82. Internal and external factors also contribute to the students’ speaking skills.